Dispersion compensation using the inverse transfer function of fiber optic channel - (:unkn) unknown (Istanbul University, 2009)
In this article, we examined the attenuation and chromatic dispersion induced pulse broadening during soliton pulse propagation in a single mode fiber (SMF) neglecting the nonlinearity effect. It is shown by simulation that this pulse broadening and attenuation problems can be eliminated using a proposed equalizer even the dispersion parameter of the fiber changes during pulse propogation. For this purpose, Nonlinear Schrödinger Equation (NLS) that characterizes pulse propagation in optical fibers was solved numerically in Matlab environment with the developed software using split-step Fourier method and the simulation results were shown grafically in 3-D format. Using the simulations results, it is observed that the soliton impulse is distorted by broadening and attenuation proportional to the fiber length.The proposed equalizer compansates these distorsions by narroving pulse width and increasing the pulse level to the initial value for fiber cable lengths up to 120 km but can not be sucessful for longer fiber lengths. We are planning to apply this equalizer for OFDM signals.
Keywords: Chromatic dispersion compensation; Electronic equalizer; Fiber optic transmission; Soliton